Naringenin enhances the efficacy of human embryonic stem cell-derived pancreatic endoderm in treating gestational diabetes mellitus mice - Bao-heng Xing; Feng-zhen Yang; Xiao-hua Wu (Elsevier, 2016)
Gestational diabetes mellitus (GDM) is a disease commonly occurs during mid to late pregnancy with pathologies such as hyperglycemia, hyperinsulinemia and mal-development of fetus. We have previously demonstrated that pancreatic endoderm (PE) derived from human embryonic stem cells (hESCs) effectively alleviated diabetic symptoms in a mouse model of GDM, although the clinical efficacy was limited due to oxidative stress. In this study, using the anti-oxidant agent naringenin, we aimed to further enhance the efficacy of hESC-derived PE transplant. Insulin-secreting PE was differentiated from hESCs, which were then transplanted into GDM mice. Naringenin was administered to mice receiving the PE transplant, with sham operated mice serving as negative control, to assess its effect on alleviation of GDM symptoms. We found that naringenin supplement further improved insulin response, glucose metabolism and reproductive outcome of the PE-transplanted female mice. Our new findings further potentiates the feasibility of using differentiated hESCs to treat GDM, in which anti-oxidative agent such as naringenin could greatly enhance the clinical efficacy of stem cell based therapies.